Sennacherib, King of Assyria - Elayi, Josette (Archaeology and Biblical Studies, 2018)
Cover -- Contents -- Abbreviations -- Chronology of Sennacherib's Reign -- Introduction -- Portrait of Sennacherib -- Sennacherib, the Crown Prince -- Accession and Priority Campaigns (705-701) -- Consolidating the Empire (700-695) -- Focusing on Babylonia and Its Allies (694-689) -- End of Reign (688-681) -- Traditions and Reforms -- Building and Innovation -- Conclusion: Assessment of Sennacherib's Reign -- Selected Bibliography -- Index of Ancient Sources -- Index of Modern Authors -- Index of Personal Names